Impedance in isolated mouse lungs for the determination of site of action of vasoactive agents and disease - Vanderpool, Rebecca R. (2010)
Hypoxic pulmonary hypertension is a disease of the lung vasculature that is usually quantified by pulmonary vascular resistance (PVR). However, a more complete description of lung vascular function and right ventricular afterload is provided by pulmonary vascular impedance (PVZ) from spectral analysis of pulsatile pressure-flow relationships. We studied pulsatile pressure-flow relationships in isolated, perfused lungs of mice in normoxia, after induction of hypoxic pulmonary hypertension by 10 days of hypoxic exposure, and after the administration of the vasoactive agents sodium nitroprusside and serotonin in order to gain insight into the effects of disease and vasoactive agents on afterload. Chronic hypoxia exposure increased 0 Hz impedance (Z(0)) from 2.0 ± 0.2 to 3.3 ± 0.2 mmHg min/ml but decreased characteristic impedance (Z(C)) from 0.21 ± 0.02 to 0.18 ± 0.01 mmHg min/ml (both P<0.05). Sodium nitroprusside only slightly decreased Z(0) but increased Z(C) in normal lungs (P<0.05) and did not affect Z(C) and decreased Z(0) in hypertensive lungs (P<0.05). Serotonin increased Z(C) in normal and hypertensive lungs but decreased Z(0) in hypertensive lungs (P<0.05). There was an inverse correlation between mean pulmonary artery pressure and Z(C) in all circumstances. These findings demonstrate that vasoactive interventions can have different sites of action (i.e., proximal vs. distal segments) in the normal and chronically hypoxic pulmonary vasculature, and the pressure-dependency of Z(C) and R(W). The measurement of PVZ in isolated lungs allows for an improved understanding of the modes of action of drugs and hypoxia on the pulmonary circulation.